Assessment of axonal injury in multiple sclerosis: combined analysis of serum light-chain neurofilaments and diffusion tensor imaging - Mohammadreza Sharifi; Milad Jalilian; Mohammadreza Elhaie; Iraj Abedi (BMJ Neurology Open)
Background Multiple sclerosis (MS) is a chronic neuroinflammatory condition characterised by demyelination and axonal damage in the central nervous system. Diffusion tensor imaging (DTI) enables non-invasive investigation of microstructural white matter alterations, while serum neurofilament light chain (NFL) holds promise as a fluid biomarker of axonal injury.Objectives To use DTI and serum NFL measurements to evaluate white matter pathology in patients with MS and explore the relationship between in vivo imaging and biochemical indicators of axonal damage.Methods 41 patients with relapse-remitting MS and 41 age-matched healthy controls underwent brain MRI including DTI acquisition. Serum samples were analysed for NFL concentrations using ELISA. Region of interest analysis was conducted to derive DTI metrics including fractional anisotropy, mean diffusivity, axial diffusivity and radial diffusivity. Correlational analyses were used to explore the associations between the imaging and biochemical indices.Results Patients exhibited significantly elevated serum NFL levels and altered DTI metrics compared with controls, indicative of axonal/myelin pathology. DTI parameters were positively correlated with serum NFL concentration (p value<0.0001). Visual analogue scale scores demonstrated a significant positive relationship between DTI metrics and NFL, validating their potential as radiological and fluid-based markers of symptom severity.Conclusions Combined DTI and serum NFL measurements may enhance the evaluation of axonal injury in MS by providing complementary in vivo and biochemical perspectives. The corresponding changes observed between the modalities support their utility as non-invasive biomarkers reflecting pathophysiological processes and clinical status in MS. Larger validation cohorts are needed to determine the clinical applicability.